Educational priorities in a post pandemic world - Kobylarek, Aleksander; Plavčan, Peter; Amini Golestani, Taher (Journal of Education Culture and Society, 2021)
This article attempts to bring together the most important educational priorities which should be taken into consideration when planning education in a world recovering from a pandemic. Some of the priorities discussed here should have already been taken into account during the 20th century, whilst others are completely new and result from changes that have come about in the 21st century, such as increased arrogance, ignorance, authoritarianism, educational insecurity, contempt for nature, confusion and the promotion of the lies under the name of post-truth . The authors propose a holistic approach to the education process, focused on priorities. In turn, the definition of those priorities should result from the most important problems that affect humanity.